Republic of Serbia : Sixth Review Under the Stand-By Arrangement and Modification of the Arrangement Review Schedule-Press Release; Staff Report; and Statement by the Executive Director for the Republic of Serbia. (IMF Staff Country Reports; Country Report, 2016)
This paper discusses Serbia's Sixth Review Under the Stand-by Arrangement and Modification of the Arrangement Review Schedule. The program remains on track, and the economy continues to strengthen. Significant fiscal overperformance and renewed efforts to address structural weaknesses have helped boost confidence. This, along with a healthy credit recovery on the back of substantial monetary policy easing, has helped restore robust growth, while persistently low inflation has reinforced recovery in real incomes. Public debt has started to decline. The IMF staff supports the authorities' request for the completion of the sixth review under the Stand-by Arrangement and a shift to semiannual review.